Brain Delivery of Thyrotropin-Releasing Hormone via a Novel Prodrug Approach - Katalin Prokai-Tatrai; Daniel L. De La Cruz; Vien Nguyen; Benjamin P. Ross; Istvan Toth; Laszlo Prokai (MDPI AG, 2019)
Using thyrotropin-releasing hormone (TRH) as a model, we explored whether synergistic combination of lipoamino acid(s) and a linker cleaved by prolyl oligopeptidase (POP) can be used as a promoiety for prodrug design for the preferential brain delivery of the peptide. A representative prodrug based on this design principle was synthesized, and its membrane affinity and in vitro metabolic stability, with or without the presence of a POP inhibitor, were studied. The in vivo formation of TRH from the prodrug construct was probed by utilizing the antidepressant effect of the peptide, as well as its ability to increase acetylcholine (ACh) synthesis and release. We found that the prototype prodrug showed excellent membrane affinity and greatly increased metabolic stability in mouse blood and brain homogenate compared to the parent peptide, yet a POP inhibitor completely prevented prodrug metabolism in brain homogenate. In vivo, administration of the prodrug triggered antidepressant-like effect, and microdialysis sampling showed greatly increased ACh release that was also antagonized upon a POP inhibitor treatment. Altogether, the obtained promising exploratory data warrant further investigations on the utility of the prodrug approach introduced here for brain-enhanced delivery of small peptides with neurotherapeutic potential.